(untitled) - Sokal, Robert R. (New York, 1995)
In addition to the incorporation of computer calculation, this new edition features: a chapter on handling data that has been updated to stay current with the development of computer hardware and software; the expansion of a number of important topics, including the revised Kolmogrov-Smirnov test, the Mantel-Haenszel procedure and logistical regression; and the inclusion of additional homework exercises to provide students with more practice and more illustration
Keywords: Biometry